2015
DOI: 10.1021/acs.biomac.5b00145
|View full text |Cite
|
Sign up to set email alerts
|

Water-Resistant, Transparent Hybrid Nanopaper by Physical Cross-Linking with Chitosan

Abstract: ABSTRACT. One of the major, but often overlooked, challenges towards high end applications of nanocelluloses is to maintain their mechanical stability under hydrated conditions. As such, permanent covalent crosslinking or surface hydrophobization are viable solutions provided that neither processability nor interfibrillar bonding is compromised. Here we show an alternative based on physical crosslinking of nanofibrillated cellulose (NFC, also denoted as microfibrillated cellulose, MFC, and cellulose nanofibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
104
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(105 citation statements)
references
References 65 publications
1
104
0
Order By: Relevance
“…Those results are in line with previous reports in which it is shown that the tensile modulus of the nanopaper increases at expense of ductility when it is reinforced with stiff nanoparticles . In this framework, the improvement of the CNC-ZnO particle interaction by chemical modification of zinc oxide would lead to a more favourable stress-transfer across the nanopaper structure, increasing the fracture toughness (Toivonen et al, 2015). Performed mechanical tests confirm the high strength of fabricated nanopapers, which show higher Young modulus than many synthetic polymers such as polystyrene, polyethylene and polyethylene terephthalate (Briston, 1988).…”
Section: Mechanical Properties Under Axial Tensile Stressmentioning
confidence: 99%
“…Those results are in line with previous reports in which it is shown that the tensile modulus of the nanopaper increases at expense of ductility when it is reinforced with stiff nanoparticles . In this framework, the improvement of the CNC-ZnO particle interaction by chemical modification of zinc oxide would lead to a more favourable stress-transfer across the nanopaper structure, increasing the fracture toughness (Toivonen et al, 2015). Performed mechanical tests confirm the high strength of fabricated nanopapers, which show higher Young modulus than many synthetic polymers such as polystyrene, polyethylene and polyethylene terephthalate (Briston, 1988).…”
Section: Mechanical Properties Under Axial Tensile Stressmentioning
confidence: 99%
“…

high tortuosity and complex flow channels, which may cause high flow resistance, specifically due to agglomeration when the reactant gas flows through the Ni catalysts. [34][35][36][37] Mechanically superstrong composites have been demonstrated by incorporating cellulose nanofibers. For example, transparent films based on cellulose nanofibers are promising replacements of plastics for biodegradable electronics.

…”
mentioning
confidence: 99%
“…The lack of applications of chitosan fibers were the poor mechanical and stability of dressing chitosan fibers/fabrics as well as to prepare 3D structure of chitosan has to be chemically cross-linked by different hazardous cross-linker (Lee et al, 2004;Schiffman and Schauer, 2007;Yang et al, 2005). Almost all studies of chitosan based wound dressing only used on form of fibers (micro/nano) (Annur et al, 2015;Schiffman and Schauer, 2007;Toivonen et al, 2015;Zhang et al, 2008), films (Ligler et al, 2001;Mi et al, 2006;Suginta et al, 2013;Yuan et al, 2007) or hydrogel (Jungst et al, 2015;Kumar et al, 2004;Suginta et al, 2013), but chitin/chitosan-glucan microfibers/nonwoven mats not been reported. Therefore, in the present research we dissolve the complex for the first time in green solvent, and to innovate complex-based wound dressing with improved the bacteria killing and to enhance the healing properties.…”
mentioning
confidence: 99%